2020
DOI: 10.1101/2020.02.17.953331
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sphingolipids regulate the tethering stage of vacuole fusion by affecting membrane fluidity

Abstract: ORCIDRutilio Fratti -https://orcid.org/0000-0001-9109-6666 Running title: Elo3p regulation of vacuole fusion via lipid rafts SummaryMany sphingolipids contain very-long chain fatty-acids with 26 carbons. The deletion of Elo3, the elongase that adds the final two carbons results in pleiotropic effects that negatively alter membrane fusion at the tethering and docking stages. AbstractThe role of sphingolipids in controlling the endolysosomal membrane trafficking remains unclear. Here, we show that in Saccharomyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 192 publications
1
3
0
Order By: Relevance
“…This effect was most pronounced in wild-type cells, where the contribution of multi-vesicular vacuoles went from 25.34% in the absence to more than 60% for the uncorrected data ( Figure 2A ) and 80% for the corrected data ( Figure 2B ) in the presence of myriocin. This result confirms earlier observations, which showed that sphingolipids and very long chain bases are essential for vacuole fusion [ 17 ]. Interestingly, myriocin had a slightly milder effect in both ncr1Δ and npc2∆ cells ( Figure 2 ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This effect was most pronounced in wild-type cells, where the contribution of multi-vesicular vacuoles went from 25.34% in the absence to more than 60% for the uncorrected data ( Figure 2A ) and 80% for the corrected data ( Figure 2B ) in the presence of myriocin. This result confirms earlier observations, which showed that sphingolipids and very long chain bases are essential for vacuole fusion [ 17 ]. Interestingly, myriocin had a slightly milder effect in both ncr1Δ and npc2∆ cells ( Figure 2 ).…”
Section: Resultssupporting
confidence: 93%
“…This could be the direct consequence of impaired delivery of ergosterol into the vacuole membrane in the absence of the Ncr1-Npc2 transport system, in line with our previous results, and the absolute requirement of ergosterol for vacuole fusion [ 8 , 43 , 44 ]. Alternatively, it could be the consequence of other factors, such as a disturbed sphingolipid homeostasis, altered TORC signaling or changed iron availability, which all have been observed in ncr1Δ cells [ 16 , 17 , 45 , 46 ]. To explore such possibilities, we have used inhibitors of the aforementioned processes and assessed their impact on vacuole fusion status in wild-type cells and in cells lacking either Ncr1 or Npc2 under starvation conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Saccharomyces cerevisiae, for example, VLCFAs are associated with the highly curved membrane structures, which appear to be especially important in the endo-lysosomal pathway (Obara et al, 2013;Schneiter et al, 2004). The yeast cells lacking Elo2 or Elo3 display morphological and vacuolar defects (Chung et al, 2003;Hurst et al, 2020). Recently, VLCFAs have been reported to be critical for mating (Villasmil et al, 2016(Villasmil et al, , 2017, osmotic tolerance (Zhu et al, 2020), cell survival and oleic acid-mediated cytotoxicity (Wang et al, 2018) in S. cerevisiae.…”
Section: Introductionmentioning
confidence: 99%